Sesquiterpene Lactams and Lactones With Antioxidant Potentials From Atractylodes macrocephala Discovered by Molecular Networking Strategy - Wang, Pan; Zhao, Yi-nan; Xu, Rui-zhu; Zhang, Xiao-wei; Sun, Yi-ran; Feng, Qing-mei; Li, Zhong-hua; Xu, Jiang-yan; Xie, Zhi-shen; Zhang, Zhen-qiang; E, Heng-chao (Frontiers in Nutrition, 2022)
Atractylodes macrocephala rhizome (called Bái-zhú in China) have a long history as functional food and herbal medicine in East Asia, especially in China. We present a molecular network strategy to further explore the unknown sesquiterpenoids of A. macrocephala rhizome. Two new nitrogen-containing sesquiterpenoids, atractylenolactam A (1) and atractylenolactam B (2), two new sesquiterpene lactones 8-methoxy-atractylenolide V (6) and 15-acetoxyl atractylenolide Ⅲ (7), along with twelve known analogues (3–5 and 8–16), were discovered and isolated. All structures were assigned on the basis of detailed spectroscopic analyses. The absolute configuration of 1, 2, 6, and 7 were established by TDDFT-ECD calculations. All these compounds have different degrees of activation on nuclear-factor-E2-related factor-2 (Nrf2) with concentration-dependent.